SUBCONTRACTOR COMPETENCY MANAGEMENT STRATEGY IN HEAVY EQUIPMENT RENTAL AND COAL HAULING SERVICE COMPANIES USING A THEMATIC APPROACH AND EXPLORATIVE SWOT (Case Study at PT Mutiara Tanjung Lestari) - Verianto; Farida Yuliaty (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Purpose – This study aims to formulate an effective and sustainable subcontractor competency management strategy at PT Mutiara Tanjung Lestari, a heavy equipment and hauling services company in Kalimantan. Methodology – The research approach used was descriptive qualitative with thematic analysis and exploratory SWOT analysis methods. Data were obtained through in-depth interviews with five key informants from management and subcontractors. Findings – The results of the thematic analysis indicate that the main obstacles lie in suboptimal onboarding, irregular technical training, weak supervision of SOP-K3, and the lack of consistent evaluation and feedback mechanisms. The SWOT results indicate that the company's strategic position is in Quadrant II (Weakness-Opportunity), so the recommended strategy is diversification, namely utilizing external opportunities to overcome internal weaknesses. This study produces four alternative strategies for managing subcontractor competencies that can be implemented in an integrated manner. Originality – These findings are expected to be a practical reference in developing subcontractor management in the mining services sector